2021
DOI: 10.3390/agriculture11090857
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Decision-Making on the Concept of Coexistence: A Comparative Analysis between Organic and Biotech Farmers in the Philippines

Abstract: Farmer perspectives are relevant for understanding agricultural issues and formulating policies. In this study, we conducted a cross-sectional survey on 70 Filipino farmers (i.e., 35 organic and 35 biotech) to understand farmers’ perspectives regarding coexisting farming methods. Internal response variables were tested to verify the type of decision-making processes being undertaken by biotech and organic farmers. Our results showed that a non-linear decision-making process, similar to the Stimulus–Organism–Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…Farmers need to generate enough income to maintain their livelihoods, invest in their farms, and respond to changes in the climate. This aligns with the sentiments of other studies, stating that while giving priority to environmentally friendly farming methods may be beneficial in the long run, its sustainability may be hindered when farmers are resource-constrained and experience income reduction due to less agricultural productivity [26,27]. Therefore, economic sustainability is a critical component of ECA that could potentially affect farmers' adoption of ECA practices.…”
Section: Economic Sustainability Of Ecasupporting
confidence: 80%
“…Farmers need to generate enough income to maintain their livelihoods, invest in their farms, and respond to changes in the climate. This aligns with the sentiments of other studies, stating that while giving priority to environmentally friendly farming methods may be beneficial in the long run, its sustainability may be hindered when farmers are resource-constrained and experience income reduction due to less agricultural productivity [26,27]. Therefore, economic sustainability is a critical component of ECA that could potentially affect farmers' adoption of ECA practices.…”
Section: Economic Sustainability Of Ecasupporting
confidence: 80%
“…Indeed, the perception of being involved in a bigger cause is shaped by farmers' individual differences and environmental influences. This was shown in another study conducted in the Philippines that focused on farmers' perspectives on coexisting farming methods, which observed that groups of farmers are affected differently by internal and external factors [25]. Therefore, this enhances the need to understand farmers' perspectives and opinions, which in turn affect their involvement in various agricultural programs.…”
Section: Globally Important Agricultural Heritage Systems (Giahss) In Japan and Their Impact On Farmer Involvementmentioning
confidence: 93%
“…Respondentdriven sampling-a specialized form of snowball sampling-was used to track down the target respondents of the study, with the help of government officials and farmer leaders. This employed a similar sampling approach used in previous studies that also tracked down and interviewed biotech corn farmers [27,28].…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…The results of the correspondence analysis concur with this since farmers who perceive the ban as incorrect are more inclined to continue their biotech corn adoption. Indeed, previous studies on biotech farmers emphasized the importance of knowledge and satisfaction for continued adoption [27,28]. Furthermore, major scientific organizations worldwide have attested to the safety of biotech crops.…”
Section: Farmers' Decision-making Process and Factors Affecting Farme...mentioning
confidence: 99%